The Effect of Effective Interpersonal Communication Training on Psychological Symptoms (Stress, Anxiety, Anger, and Depression) In Incompatible Couples - Darvishizade, Majid; Bahadur, Sarah; Shavisizad, Saeed (Shahroud Journal of Medical Sciences, 2025)
Background: One of the causes of marital problems is the lack of communication skills between couples; communication encompasses the entire life of a person. Life begins with the beginning of communication and ends with its termination. This study was conducted with the aim of investigating the effect of effective interpersonal communication training on psychological symptoms (stress, anxiety, anger, and depression) in incompatible couples referring to counseling centers.Methods: This study was a quasi-experimental pre-test and post-test study with a control group. The sample size was 40 people who were selected from the aforementioned population using convenience sampling. 20 people were assigned to the experimental group and 20 to the control group. The research tools used were psychological symptom questionnaires. The experimental group received effective interpersonal communication training weekly for 8 1.5-hour sessions. After collection, the data was entered into SPSS 18 and analyzed using descriptive and analytical statistics.Results: The results confirm that there is a significant difference between the experimental and control groups in terms of the post-test dimensions of psychological symptoms (stress, anxiety, anger, and depression) compared to the pre-test control. Accordingly, it can be said that a significant difference has been created in at least one of the dependent variables, namely the dimensions of psychological symptoms (stress, anxiety, anger, and depression), and the effect coefficient shows that 66.9% of the difference between the two groups is related to the experimental intervention. Therefore, communication skills training helps the individual to have a better understanding of himself and to better adapt to others. It is also important in personal and professional communications. This skill helps a person express their opinions, beliefs, desires, needs, and emotions and ask for help and guidance from others when needed. The skill of asking for help and guidance from others in times of need is an important factor in a healthy relationship.Conclusion: Based on the results of the study, it can be stated that interpersonal skills training plays an important role in understanding each other and appropriate planning should be done to implement these trainings for couples.